Cavity-enhanced optical methods for online microfluidic analysis - Rushworth, C; Davies, J; Cabral, J; Dolan, P; Smith, J; Vallance, C (2012)
Absorption spectroscopy is potentially an attractive detection technique for microfluidic applications, as it is universal, label-free, and rapid. However, the short optical pathlength through a microfluidic channel often imposes unacceptable limits on the detection sensitivity. We review a variety of strategies for increasing the pathlength and thereby improving the detection sensitivity of absorption measurements, covering extended-pathlength single-pass methods, multi-pass measurements, and finally a range of cavity-enhanced methods. We conclude that cavity-enhanced approaches show considerable promise for applications in which a high detection sensitivity is required within a small probed volume. © 2012 Elsevier B.V. All rights reserved.